2023
DOI: 10.1007/s00432-023-04707-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on reported cancer diagnoses in Bavaria, Germany

Abstract: Purpose The aim of our study was to explore the impact of the COVID-19 pandemic on reported cancer cases in Bavaria, Germany, by comparing pre-pandemic (March 2019 to February 2020) and pandemic period (March 2020 to February 2021). Methods Data on incident cases were retrieved from the Bavarian Cancer Registry (until 22nd April 2022). We included patients with malignant and in situ neoplasms reported by pathology departments with consistent reporting. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…А number of European countries, Canada, and the USA during 2020-2023 have reported similar significant declines in the cancer incidence rates observed or the number of new cancer cases detected in 2020, particularly in the spring of 2020 during the first COVID-19 lockdowns [10][11][12][13][14][15][16][17][18][19][20][21][22]. They used the data of cancer registries, pathology departments, and the number of suspected cancer referrals for diagnostics or referrals for oncological services.…”
Section: Discussionmentioning
confidence: 99%
“…А number of European countries, Canada, and the USA during 2020-2023 have reported similar significant declines in the cancer incidence rates observed or the number of new cancer cases detected in 2020, particularly in the spring of 2020 during the first COVID-19 lockdowns [10][11][12][13][14][15][16][17][18][19][20][21][22]. They used the data of cancer registries, pathology departments, and the number of suspected cancer referrals for diagnostics or referrals for oncological services.…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID-19 pandemic affected different nations and geographical areas to different degrees, the results of this landmark study are not necessarily indicative of the situation in Germany. Some literature suggests that the impact of COVID-19 was limited to certain tumor entities and not all diagnoses were equally affected by the pandemic in Germany (Voigtländer et al 2023 ; Jacob et al 2022 ; Piontek et al 2021 ). Jacob et al ( 2022 ) compared the number of patients diagnosed with cancer in general and specialized practices in Germany in April 2020-March 2021 (COVID-19 era) and April 2019-March 2020 (pre-COVID-19 era).…”
Section: Introductionmentioning
confidence: 99%
“…Jacob et al ( 2022 ) found a significant decrease in the number of patients diagnosed with skin cancer (12.8% reduction), not of patients diagnosed with lip, oral cavity, and pharynx cancer. Voigtländer et al ( 2023 ) analyzed the impact of the pandemic on reported cancer cases in Bavaria and compared cancer cases of the pre-pandemic period (March 2019 to February 2020) and pandemic period (March 2020 to February 2021).Significant reductions were found for colon, rectum, and skin/melanoma (> 10% reduction) without a decrease in lip, oral cavity, and pharynx cancers. The majority of these studies were restricted to data obtained in the first wave of the pandemic and up to February 2021 limiting the generalizability of the results to the whole period of the pandemic.…”
Section: Introductionmentioning
confidence: 99%